Regioselective nitration of cumene to 4-nitro cumene using nitric acid over solid acid catalyst - Mathew, Sanyo M.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Catalysis Communications, 2006)
The regioselective nitration of cumene to 4-nitro cumene (4-NC) has been carried out using 70% nitric acid over MoO3/SiO2 solid acid catalyst with high conversion (62%) and selectivity (68%) for 4-NC. A series of MoO3/SiO2 catalysts with different MoO3 loadings (1-20 mol%) were prepared by sol-gel technique and characterized using different characterization techniques. XRD analysis revealed the amorphous nature of the catalyst up to 10-mol% MoO3 loading and formation of alpha-MoO3 crystalline phase on amorphous high surface area mesoporous silica support at higher MoO3 loading. Maximum conversion and selectivity has been obtained with slower addition of nitric acid and simultaneous azeotropic removal of water formed during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cumene; nitration; ring nitration; side chain nitration; solid acid catalyst

Recovery of ammonical salts from mother liquid of 2-methyl-5-nitroimidazole - Dongare, Mohan K.; Rode, C. V.; Chandorkar, J. G. (Asian Journal of Chemistry, 2008)
An attempt have been made to recover the ammonical salt (ammonium sulphate and ammonium nitrate) from the mother liquid of 2-methyl-5-nitroimidazole successfully.
Keywords: 2-methyl-5-nitroimidazole; ammonium nitrate; ammonium sulphate; Recovery

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR